Developing an Ethical Model of Care for People with a Variation of Sex Development in Switzerland. (20th October 2021) - Kraus, C; Meyrat, BL
Abstract: Background: What constitutes best practice in the area of intersex, renamed Disorders/differences of sex development (DSD/dsd) or even variations of sex development (VDS) after the "Chicago consensus"? What kind of model of care would meet the requirements of an ethical management of intersex/dsd/VDS? Methods: In 2005, we launched an interdisciplinary SHS and gender medicine project to improve the standards of care for persons with intersex/dsd/VDS. Abroad, this project, initiated in Lausanne, has sometimes been called the "Swiss Model". It includes the development of an interdisciplinary team, based at the University hospital CHUV, who takes care of persons born with intersex/dsd/VDS and also teaches an ethical model of care to students at the Medical School of the University of Lausanne. The "Swiss Model" is centered on the children's fundamental rights to bodily integrity, self-determination and genital autonomy. We describe our 10 years' experience, the reasons, goals and development modalities of our team and model of care. Results: We have developed a medical ethics "from below" to overcome the lack of ethical recommendations, as it was the case until 2012 in Switzerland. During this period of time, genital surgeries and other non-vital medical treatments have been postponed until the child could fully participate in the medical decisions and give one's informed assent or consent. Only one family did not follow our recommendations. Conclusions: The Lausanne experience testifies to the possibility of changing the so-called Johns Hopkins paradigm in actual practice. The model of care we have implemented can define best practice as it is scientifically grounded, medically reasonable, and ethically consistent.